Cancer‐related pain management: A review of knowledge and attitudes of healthcare professionals. (27th December 2016) - Kasasbeh, M. A. M.; McCabe, C.; Payne, S.
Abstract : Cancer‐related pain (CRP) is common and many patients continue to experience pain in spite of advances in pain management modalities. The lack of knowledge, inadequate assessment of CRP and/or organisational factors, such as lack of time due to heavy workload, can be a barrier to effective pain management of healthcare professionals. The purpose was to examine the evidence with regard to the knowledge and attitudes towards practice of healthcare professionals in relation to CRP management. A search of the literature (1999–2015) was conducted searching databases and journals including CINAHL, MEDLINE, PsycINFO, PubMed, Science Direct and Wiley‐Blackwell. The initial search revealed a total of 99 articles and following removal of those that did not meet the inclusion criteria, 19 articles were included in the final review. Recognition of the widespread under treatment of CRP has prompted recent corrective efforts in terms of education from healthcare professionals, however, there is a continuing deficit in healthcare professionals' knowledge with regard to CRP management and indicated that healthcare professionals still have negative attitudes that hinder the delivery of quality care to patients suffering from CRP. Further research on how and where education on this topic should be delivered is required.